Islamic Criminal Law Principles in Regulation of Misuse Information on Social Media Victims - Mayada Afriga Arum Dari; Nadya Melinda Oktarina (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
Law Number 11 of 2008 has an important role in the realization of building a cyber regime. Cases of data misuse on social media are rife along with the development of technology. According to the detikinet page, at least 14 million social media accounts were affected by personal data leaks. In Islam, abuse of identity without the consent of the party is one of the actions that prohibited by Allah SWT, this is because it’s an act that damages and causes harm to other people. The purpose of this study is to find out the form of handling cybercrime in Indonesia, to find out the perpetrators accountability of data misuse according to the ITE Law, and to find out the responsibility for misusing information data on social media according to Islamic Criminal Law. The research method used is a qualitative approach with library research, the data sources used are primary and secondary data sources. Technical data collection by collecting data from primary and secondary sources, namely with a conceptual approach. Research results 1) The form of handling Cybercrime can be carried out with the obligation of operators to provide education to users 2) ITE crimes are regulated in 9 Articles, from Article 27 to Article 35. In these 9 articles, 20 forms are formulated/ type of ITE crime. 3) Accountability for data misuse on social media included in the ta'zir category for violations. The appropriate sanction according Islamic law is imprisonment, also additional punishment in the form of a fine.